REVIEW OF BIOLOGICAL ACTIVITIES OF HYDRAZONES - Ali, Md. Rahmat; Marella, Akranth; Alam, Md. Tauquir; Naz, Ruksar; Akhter, Mymoona; Shaquiquzzaman, Md.; Saha, Rikta; Tanwar, Omprakash; Alam, Md. Mumtaz; Hooda, Jyoti (Indonesian Journal of Pharmacy, 2012)
Hydrazones possess an azomethine  –NHN=CH   group  and are  considered  as derivatives  of aldehydes and  ketones  in which the  oxygen  atom  has  been  replaced  by  the  NNH2 functional group. These are widely studied molecules owing to their ease of preparation  and  diverse  pharmacological  potential.  This  has  led researchers  to  synthesize  different  heterocyclic  compounds bearing  hydrazones.  Medicinal  chemists  across  the  world  have done  immense  work  on  hydrazones  and  developed  agents  with better  activity  and  low  toxicity  profiles.  Following  different synthetic  protocols  and  through  proper  SAR  studies  differently substituted  hydrazones  have  been  developed  and  found  to  be active  against  different  pharmcological  targets.  They  are  known to  possess  different  biological  activities  viz.  antimicrobial,  antiinflammatory,  anticancer,  antimalarial  etc.  These  observations have  been  guiding  for  the  development  of  new  hydrazones  that possess  varied  biological  activities.  The  review  aims  at highlighting the diverse biological activities of hydrazones.Key words: Azomethine, Hydrazones, Pharmacological Potential